Philippines : Financial Sector Assessment Program-Technical Note on Risk Assessment of Banks, Non-Financial Corporates, and Macro-Financial Linkages. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The Philippines is a dynamic economy with a relatively smaller financial system than other Asian emerging market economies, dominated by banks. The total assets of the system amount to 126 percent of GDP. However, bank credit is just over 50 percent of GDP and mostly goes to nonfinancial corporates (NFCs). Banks are also tightly interlinked with NFCs through conglomerate ownerships. Access to finance for individuals is significantly lower than comparator systems, with only a third of adults having formal accounts. Non-bank financial institutions and capital markets-especially bond markets-are substantially less developed than banks. The Fintech ecosystem is nascent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Philippines